A Study on Employer Branding Through Social Media: Exploring the Impact of Social Media on Employer Branding (Journal of Advances and Scholarly Researches in Allied Education, 2020)
For businesses who wish to make them recognizable as fascinating employers and to hire prospective workers, utilizing more traditional tactics used by work seekers and relaters is increasingly essential to the attention and influence of the social network. This study seeks to examine the immediate future of branding employers using social networking, as the academic envisages. Employer branding is now as relevant on the market as products or services. In this study we have discussed about the Origin of employer branding and discussing of employer brand, Employer branding in social media Strengthens Your Employer Brand, Employer Branding and Social Networking Sites, Conceptualizing employer branding, Social media used in employer brand communication, Using social media in hiring Benefits and risks Employer It provides a nice look by using different social networking platforms such as Face book, Twitter, YouTube and Google+ to build a better working experience for people with a good working environment. The branding of Employers helps the organization, since the seekers choose that employer that trust their workforce and provide a greater career prospects the most skilled and retention rate.